Conflicts in the Niger Delta : implications for regional security - Adams, Isiaka Abiodun; Hossain, Ishtiaq (2010)
The protracted conflict in the oil rich Niger Delta area in Nigeria and the Gulf of Guinea harbours complex implications for security in the region. At the centre of the conflict is the agitation by the mainly Ijaw and Ogoni ethnic nationalities for mineral resource control, national self-determination and/or more robust constitutional integration into the Nigerian state, environmental rights and mitigation of extant degradation, as well as quest for institutionalisation of genuine federal fiscal policy and practice. Relying on the Regional Security Complex Theory (RSCT), with its emphasis on human and environmental security as compared with traditional state-centred security, the article argues that if allowed to exacerbate, the conflict portends grave danger and transnational security challenge for Nigeria, the West African sub-region and the entire continent, considering the huge population and the geo-strategic status of Nigeria. The efforts of the Nigerian state in addressing the lingering crisis and the role of external powers in engendering peace in the region also come under focus. The authors call for holistic proactive measures to stem the conflicts from escalation and spread to the entire region. The paper is divided into five sections: Firstly, it presents the concept, meaning and nature of RSCT; secondly, it justifies the application and relevance of RSCT to the study and understanding of security threats; thirdly, it examines the characteristics of RSC; fourthly, it explains regional security challenges and then suggests mechanisms to deal with those in the West African region; and fifthly, it assesses the effectiveness or otherwise of the measures adopted by the Nigerian state to confront the challenge as well as suggest policy options for an enduring peace in the Niger Delta area and the Gulf of Guinea.